2020
DOI: 10.18632/aging.103243
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DSCAM-AS1 promotes colorectal cancer progression by acting as a molecular sponge of miR-384 to modulate AKT3 expression

Abstract: Down Syndrome Cell Adhesion Molecule antisense1 (DSCAM-AS1), a novel long non-coding RNA (lncRNA), reportedly contributes to the development and progression of several cancers. There is a lack of information on its biological role and regulatory mechanism with respect to colorectal cancer (CRC). Here, we discovered that the expression of DSCAM-AS1 exhibited a significant upregulation in CRC tissues and cell lines in comparison with the corresponding control. Increased DSCAM-AS1 expression was associated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Recent studies indicated that AKT3 is distinctly overexpressed in CRC and that lncRNAs play an oncogenic role in CRC by functioning as a ceRNAs to modulate AKT3 expression 32 , 33 . In this research, a series of experiments proved that AKT3 is a target of miR-576-5p and is reciprocally associated with miR-576-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that AKT3 is distinctly overexpressed in CRC and that lncRNAs play an oncogenic role in CRC by functioning as a ceRNAs to modulate AKT3 expression 32 , 33 . In this research, a series of experiments proved that AKT3 is a target of miR-576-5p and is reciprocally associated with miR-576-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent studies have revealed that lncRNAs can affect the malignant behavior of cells (15,16). In addition, numerous studies have revealed that DSCAM-AS1 can affect tumorigenesis, but its role in EC remains unclear (7)(8)(9)17,18). Therefore, the aim of the present study was to investigate the biological functions of DSCAM-AS1 in EC.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, patients were treatment with radiotherapy, chemotherapy, or combination therapies. Estrogen receptor (ER), Lymph-vascular space invasion (LVSI) and histology type were classified by pathologists at our hospital in a blinded manner according to the criteria of previous literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Written informed consent was obtained from all enrolled patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations